Ultrastructural study of vitellogenesis of Ligula intestinalis (Diphyllobothriidea) reveals the presence of cytoplasmic-like cell death in cestodes - Yoneva, Aneta; Scholz, Tomáš; Młocicki, Daniel; Kuchta, Roman (Frontiers in zoology, 2015)
BACKGROUND: The tapeworm Ligula intestinalis (Diphyllobothriidea) is one of the most fascinating cestode parasites because it may cause parasitic castration of its second intermediate host, teleost freshwater fishes, due to inhibition of production of fish gonadotropic hormones. Large-sized (length up to 1 m) larvae called plerocercoids develop several months in the body cavity of freshwater fish and affect host behavior to facilitate transmission to the final host, a fish-eating bird. Vitellogenesis, i.e. formation of vitellocytes, is a key process in formation and nutrition of female gametes, oocytes in many flatworms, mainly parasitic Neodermata. The present study provides the first ultrastructural evidence in flatworms (Platyhelminthes) of the process that is interpreted as cytoplasmic-like cell death, i.e. a special case of programmed cell death (paraptosis) in vitellocytes of L. intestinalis. RESULTS: As molecular markers for paraptosis are not yet available, its identification was based on morphological criteria. Electron microscopy analyses revealed evident structural changes in vitellocytes associated with progressive cytoplasmatic vacuolation, swelling of the granular endoplasmic reticulum and mitochondria. In addition, the present study has shown that vitellocytes of L. intestinalis share numerous features in common with the members of other earliest evolved eucestodes. CONCLUSIONS: The present study indicates that paraptotic-like cell death may occur in parasitic flatworms (Neodermata). The presence of GER-bodies in mature vitellocytes indicates close relationship between the Diphyllobothriidea, Caryophyllidea and Spathebothriidea, which are considered as the earliest evolved groups of the Eucestoda. Beyond the general similarities, however, a number of differences exist between the morphology, chemical composition and amount of these inclusions which could be due to the variations in their embryonic development, life cycle strategies and definitive host groups.
Keywords: Paraptosis; Cestoda; Ultrastructure; Ligula intestinalis; Vitellogenesis; Diphyllobothriidea